DAKWAH AS AN INTERCULTURAL SPACE: Inclusive Islamic Outreach Practices in Japan - Masduki, Masduki (Asia-Pacific Journal on Religion and Society, 2023)
This article explores the inclusive and contextual Islamic preaching practices (da'wah) among Muslim communities in Japan, particularly those of Indonesian origin. In a predominantly non-Muslim, secular, and culturally homogeneous society, Islamic da'wah in Japan faces unique challenges that require adaptive and creative approaches. Rather than relying on doctrinal messages, Muslim communities engage in social participation, symbolic communication, and cultural dialogue, turning mosques like Tokyo Camii into centers of interfaith and intercultural exchange. Drawing from the frameworks of cultural da'wah, cross-cultural communication, and minority Muslim dynamics, this study finds that da'wah in Japan functions as a space of encounter—bridging Islamic values with Japanese cultural norms through everyday actions, symbolic gestures, and social initiatives. Despite facing stereotypes and limitations, Muslim communities respond with inclusive and humanistic strategies that emphasize coexistence over conversion. The findings suggest that da'wah in minority contexts, such as Japan, is most effective when it emphasizes social harmony, mutual respect, and cultural sensitivity. This study contributes to broader discussions on Islam in non-Muslim societies and highlights da'wah as a meaningful form of cross-cultural engagement in the Asia Pacific.